P109 Circulating MMP Activity and Lung Remodelling in LAM. (19th November 2012) - Cane, JL; Chang, WY; Gallagher, R; Gontu, V; Kumaran, M; Johnson, SR
Abstract : LAM is characterised by the progressive accumulation of lung cysts. It is possible increased proteolysis causes extra-cellular matrix breakdown leading to cyst formation. Matrix metalloproteinases (MMPs) are expressed in the lungs and serum of patients with LAM and can break down the extracellular matrix. Here we examined MMP expression and activity patients with LAM and healthy women and related MMP activity to extent and activity of lung disease. 59 patients with LAM and 32 healthy controls were recruited. Ethical approval was obtained and all gave informed consent. Serum was collected in separator tubes and processed within 30 minutes, urine was centrifuged at 4°c and all samples were stored in aliquots at –80°c. MMP-2 and –9 were measured by ELISA and gelatin zymography. Urine results were normalised against creatinine concentration prior to analysis. Lung function data was obtained from clinical records. Cyst volume was measured on a Philips MX8000 IDT 16 slice spiral CT scanner using density mask software on a Philips Healthcare Q19.5 Extended Brilliance TM Workspace. The trachea and large airways were excluded, cysts were defined as having a threshold density of <-900 Hounsfield units and cyst volume expressed as a percentage of total lung volume. Rate of decline for FEV1 was estimated from symptom detection to current lung function. Data were analysed using non parametric Mann-Whitney U tests and linear regression. Total serum MMP-2 (p<0.01), total MMP-9 (p<0.001) and active MMP-9 (p<0.05) assessed by zymography were greater in patients than controls. Urine MMP-9 did not differ. Total serum MMP-2 was associated with preserved FEV1 (p<0.01, r 2 = 0.040). Cyst volume was correlated with reduction in FEV1 and FEV1 /FVC ratio but not with any MMP measurement. Median FEV1 decline was 108.5ml/year (range 0–840): no measurement of MMP expression or activity was correlated with rate of decline. Total and active MMP-9 were raised in serum from LAM patients but were not associated with clinical course. Surprisingly, higher serum MMP-2 was associated with preserved lung function. It is not clear if circulating MMP levels reflect the situation in the lung and further analysis of MMPs as a therapeutic target for LAM is required.